Mobilizing and Activating Haíɫzaqvḷa (Heiltsuk Language) and Culture Through a Community-University Partnership - Carpenter, Jennifer; Chase, Bridget; Chung, Benjamin; Humchitt, Robyn; Turin, Mark (KULA)

(untitled) (University of Victoria Libraries, 2021)
The sharing of existing linguistic resources through online platforms has become an increasingly important aspect in revitalization projects for Indigenous languages. This contribution addresses the urgency of such work through the lens of a partnership in support of one language, Haíɫzaqvḷa (Heiltsuk), a critically endangered Wakashan language spoken in and around the traditional Heiltsuk territory of Bella Bella, British Columbia. Alongside immediate community needs for language preservation and reclamation—informed and guided by Heiltsuk values and goals—lie important ethical and practical questions about how best to activate historic recordings of Elders and knowledge holders who have now passed. Our partnership was explicitly structured around the objective of helping to mobilize the large body of existing languagedocumentation and revitalization materials created in and by the community to support broader community access through digital technologies. Working within the fast-changing digital environment requires agility in order to respond to time-sensitive goals and the strategic needs of the community. Ensuring that such work is grounded in respectful collaboration requires ongoing care, consultation and consideration. The digital landscape is still a new and exciting space, and the opportunities to use online tools and technologies in service of language revitalization are ever increasing. We believe that the strategies, approaches and modest successes of the Heiltsuk Language and Culture Mobilization Partnership may be informative for other community-based language reclamation projects. We hope that outlining our experiences and being transparent about the challenges such partnerships face may help others engaged in this urgent and timely work.